Cellular therapy in older adults with relapsed/refractory diffuse large B-cell lymphoma - Esteghamat, Naseem; Tsumura, Aaron; Marquez-Arreguin, Gabriel; Tuscano, Joseph (Frontiers in Oncology, 2024)
Relapsed/Refractory (R/R) diffuse large B-cell lymphoma (DLBCL) is an aggressive disease with poor prognosis and limited therapeutic options. High-dose chemotherapy with autologous hematopoietic stem cell transplantation (autoHCT) was historically the curative-intent treatment for patients who demonstrated chemosensitivity to salvage therapy. However, a significant portion of patients do not make it autoHCT due to disease progression or overall fitness and eligibility. This is of particular concern in the older adult population. In recent years, significant advances in cellular therapies including chimeric antigen receptor (CAR) T-cells and bispecific antibodies, in addition to improvement in autoHCT tolerability, have allowed for additional treatment options for patients with R/R DLBCL. These novel therapies offer the potential for durable remissions and cure, and should be considered in older patients. We present a review focused on the safety and efficacy of cellular therapies in the older adult population with R/R DLBCL.